The Role of Auditor Competence and Independence in Enhancing Internal Audit Quality with Auditor Ethics as a Mediating Variable - Salwa Putri Zaqiani; Dani Sopian (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research is motivated by the essential function that auditor competence and independence fulfill in enhancing the quality of internal audits. This improvement, in turn, significantly influences both organizational performance and compliance with regulatory standards. Good internal audit quality can strengthen accountability, and transparency, and foster continuous improvement within organizations. The objective of this study is to analyze the influence of auditor competence and independence on the quality of internal audits, with auditor ethics as a mediating variable. The method used is quantitative, with a population of internal auditors working in 223 Banks Perekonomian Rakyat (BPR) in West Java, and a sample of 86 auditors selected through purposive sampling. The analysis of the data was conducted utilizing Smart PLS techniques to establish the relationships between the variables and to evaluate the proposed hypotheses. The results of this research demonstrate that both the competence and independence of auditors have a substantial and direct effect on the quality of internal audits. Specifically, auditor independence plays a constructive role in fostering auditor ethics, while auditor competence serves to elevate ethical standards within auditing practices. Despite this, the direct impact of auditor ethics on the quality of internal audits is negligible, indicating that auditor ethics does not function as a mediating factor in this context. These findings underscore the essential importance of auditor competence and independence in improving the overall quality of internal audits.